Analisis Model Matematika dan Simulasi Penyebaran dan Penanganan Penyalahgunaan Narkoba di Indonesia - Ristiawan, Rifki; Endaryono, Endaryono; Mahyudi, Mahyudi (Faktor Exacta, 2024)
he increasing abuse of narcotics, psychotropic substances and addictive substances is a big problem in Indonesia today. The spread of drugs is increasing rapidly to the point that it can be considered a disaster. This research uses literature study methods and data analysis to determine assumptions and distribution models, then analyzes the models and carries out numerical simulations. A mathematical model was created to see the pattern of the spread of drug abuse and analyzed analytically to determine the existence of an equilibrium point and the type of stability, as well as to obtain the basic reproduction number . Numerical simulations were carried out to see distribution patterns in the next few years. From the results of the numerical simulations, information was obtained that to suppress the spread of drug abuse, efforts that can be made are to reduce the rate of recruitment of vulnerable classes by dealers and the rate of change from users to dealers.